Investigating insomnia as a cross-sectional and longitudinal predictor of loneliness: Findings from six samples. (July 2017) - Hom, Melanie A.; Hames, Jennifer L.; Bodell, Lindsay P.; Buchman-Schmitt, Jennifer M.; Chu, Carol; Rogers, Megan L.; Chiurliza, Bruno; Michaels, Matthew S.; Ribeiro, Jessica D.; Nadorff, Michael R.; Winer, E. Samuel; Lim, Ingrid C.; et al.
Abstract: Loneliness has been repeatedly associated with sleep problems; however, there is a dearth of research examining the prospective relationship between insomnia and loneliness, as well as this association controlling for other psychiatric symptoms. This study evaluated the cross-sectional and prospective relationship between insomnia and loneliness using six samples: 666 undergraduates; 2785 Army recruiters; 208 adults with a history of suicidality and/or depression; 343 adult psychiatric outpatients; 326 young adults at elevated suicide risk; and 183 undergraduates. A meta-analysis also was conducted to examine the magnitude of the relationship between insomnia and loneliness across the six studies. More severe insomnia symptoms were significantly associated with greater feelings of loneliness while accounting for some (e.g., anxiety, nightmares) but not all (i.e., depression) psychiatric covariates. Findings underscore the strength of the association between insomnia and loneliness and suggest that depression may account for this relationship. Additional studies are needed to further establish the temporal relationship between these variables, delineate the role of depression in the association between insomnia and loneliness, and test whether insomnia may confer unique risk for subsequent loneliness. Highlights: More severe insomnia may be associated with and predict greater loneliness. This relationship is robust but may be explained, in part, by depression symptoms. Loneliness may be useful to explore as a link in relationship between insomnia and other psychiatric problems.